Who goes first? Strategic delay and learning by waiting - Peter Wagner (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2015)
This paper considers a "war of attrition" game in which agents learn about an uncertain state of the world through private signals and from their peers. I provide existence and uniqueness results for a class of equilibria that satisfy a "full-participation" condition, and show that asymmetries in the distribution of information can lead to excessive stopping and an oversupply of information relative to the social optimum.
urn:nbn:de:bvb:19-epub-24764-2
Keywords: 330